Qualidade da água em reservatório artificial em região semiárida a partir de atributos físicos, químicos e biológicos - Rocha, Francisco Cleiton da (2015)
The macroinvertebrates are an important component of the biodiversity of aquatic ecosystems and are abundant in rivers, streams, lakes and ponds, serving as food for fish and crustaceans. The use of these organisms in the Water Quality Indices formulation (AQI's) is widely accepted and adopted in many parts of the world for monitoring water quality. The IQA's aim to present in a simple way for society, public institutions and private information generated in the monitoring. In this scenario, this study aimed to: i) study the macroinvertebrate community structure associated with species of floating macrophyte Pistia stratiotes and Eichhornia crassipes; ii) development of an AQI to the waters of Orós reservoir, where the physical, chemical and metrics of macroinvertebrates were analyzed. For this, samples were collected from surface water in seven points Orós reservoir every two months during the period from July / 2009 to July / 2011 to analysis of 29 physical and chemical properties. At the same time, it collected three samples of macrophyte Pistia stratiotes and Eichhornia crassipes for analysis of four metrics associated macroinvertebrates. After identifying the macroinvertebrates were used te analysis of variance (ANOVA) to determine possible differences in wealth metrics families and abundance. Then elaborated a IQA with the application of Principal Component Analysis (PCA) to the waters of the reservoir Orós. 3,673 bodies were found belonging to four classes and eight macroinvertebrates orders, Thiaridae family being the most abundant, expressing the deterioration of reservoir water quality. It was observed that the wealth of attributes and abundance of macroinvertebrates did not differ between the two species of weeds or between the different collection points, while the ACP promoted a reduction of 33 attributes to 24:01 explicability of 85.32% of the variance the total in five dimensions. The components expressed mainly the process of weathering and surface runoff. The IQA ranged 49-65 (regular water class), indicating that the waters of the reservoir can be used for human consumption provided that treatments are carried out. We conclude, therefore, that the IQA proposed from the set of physical and chemical attributes analyzed and the composition of benthic adequately expressed the quality of water and can be used in monitoring inserted reservoirs in the northeastern semi-arid.